Upaya Pencegahan Penyakit DBD di Kelurahan Talise Valangguni dan Kelurahan Tondo, Kota Palu - Syam, Dedi Mahyudin; Sulaeman, Djunaidil Syukur; Aryanti, Ros (Pusat Penelitian & Pengabdian Masyarakat Poltekkes Kemenkes Palu, 2025)
The aim of this Community Service activity is to increase public knowledge about preventing dengue fever and increase the Larvae Free Rate (ABJ). The activities carried out were counseling and fogging in an effort to prevent Dengue Hemorrhagic Fever (DHF) in Talise Valangguni and Tondo Villages, Palu City. The outreach method is used to convey material about dengue vector control by the Service Team to the community, in order to increase knowledge in dengue vector control. The education material is about controlling dengue vectors, both physically/mechanically, biologically, chemically and in terms of sanitation/environmental management so that the chain of transmission of vector-borne diseases can be immediately overcome. So that after the counseling is carried out, the people of Talise Valangguni and Tondo sub-districts will increase their knowledge about prevention. transmission of dengue fever. To reduce the density of the mosquito population, fogging activities were carried out in 100 houses and their surroundings with the larva free rate (ABJ) indicator. The results of the activity show that the level of public knowledge. After receiving education, the average score increased from 70.89 to 84.69 and the larvae free rate (ABJ) in monitoring increased to 96%, meaning it passed the vector environmental quality standard (ABJ≥ 95%) . From this activity, it is hoped that the people of Talise Valangguni and Tondo Villages can prevent the occurrence of dengue fever through activities to maintain environmental cleanliness.